Konsep Berinfaq Kepada Anak Yatim: Perspektif Al-Qur’an Surat al-Baqarah Ayat 215 - Yuliana Desi Rahmawati (IAIN Bengkulu, 2022)
In this modern era, it is a challenge for someone to give infaq to orphans properly and correctly. The impact of rapid changes in information technology, the proper use of social media is expected to be a means of goodness. Therefore, the use of the right concept is needed to overcome this. This research is library research and uses a descriptive-analysis method in processing the data. The results of this study, namely the concept of giving infaq al-Qur'an perspective that is offered in Surat al-Baqarah verse 215 has 3 important components, namely: giving must use good assets, must use good methods and also good goals. In addition, giving infaq to orphans should be given according to the situation and conditions, so as not to hurt their feelings. It would be nice if they were given by not publishing them on social media to minimize the negative effects of carrying out these compensation activities.